Correlation of Attitudes and Perceptions in Intermediate Reading Class Students, University of Muhammadiyah Palembang - Asti Gumartifa; Dita Adawiyah (JELLT (Journal of English Language and Language Teaching), 2022)
The enthusiasm toward reading happens as a result of good reading attitude is known as the attitude of reading. Students' reading attitudes are strongly related to their ability to be achieved by practice. The purpose of this study was to find out the correlations between students’ attitude and perception of reading in intermediate reading class. The participants were twenty-three students in the second semester of English study program, University of Muhammadiyah Palembang. The sample was taken by using purposive sampling of the even semester class in the Faculty of Teacher Training and Education. Coefficient correlation was adopted in this study. It is also intended to see if there any significant correlation between reading habits and reading perception of intermediate reading class students. The data was acquired through the use of Elementary Reading Attitude Survey (ERAS) that was established by McKenna and Kear (1990) in order to measure students’ reading attitude. An informal interview was also conducted by the researcher to acquire additional information about students' perceptions to reading. The results of this study revealed that there is moderate correlation between students' attitudes and perceptions of reading with the correlation value are 0.48. Thus, students must keep practicing and improving reading comprehension.